Pengaruh Disiplin Preventif Dan Motivasi Intrinsik Terhadap Kinerja Karyawan (Studi Pada Pt. Mitra Pedagang Indonesia Jawa Timur) - Thijanul Aroby; Iriani Ismail (Jurnal Kajian Ilmu Manajemen (JKIM), 2026)
This study aims to determine the effect of preventive discipline and intrinsic motivation on employee performance at PT. Mitra Perdagangan Indonesia. It used a quantitative method with an associative approach. Data was collected by distributing questionnaires to 50 respondents and analyzed using multiple linear regression with the help of SPSS version 25. The results showed that preventive discipline has a positive and significant effect on employees performance is 0.303 and a significance level is 0.005. Intrinsic motivation also has a positive and significant effect on employees performance is 0.550 and a significant level is 0.001 0.05. The F test showed that both variables simultaneously have a significant effect on employees performance is 0.688, and a significant value is 0.000. The results emphasize that both variables, internal motivation and preventive discipline can enhance employees performance effectively